Heterogeneity of class I beta-lactamase expression in clinical isolates of Pseudomonas aeruginosa. - Sanders, C C (1988)
Expression of chromosomal beta-lactamase was examined in 85 clinical isolates of Pseudomonas aeruginosa. beta-Lactamase assays with and without cefoxitin induction revealed four phenotypes of enzyme expression: low basal, inducible; moderate basal, inducible; moderate basal, constitutive; and high basal, constitutive. The isoelectric points of the major beta-lactamase bands were 9.4, 9.2, and 8.4. These results indicate that there is a limited heterogeneity in expression of chromosomal beta-lactamase of P. aeruginosa.